Implementasi Model Pengembangan Program Mahasiswa Wirausaha di Universitas Sahid Surakarta - Rusnandari Retno Cahyani Asri Laksmi Riani Edi Kurniadi, Destina Paningrum (PROSEDING, 2018)
Entrepreneurship is an important part of the context of the country being built. Progress or economic slump is referred to by entrepreneurs. To realize being advanced by instilling the spirit and entrepreneurial spirit of higher education that continues to be promoted and improved, by building entrepreneurial learning methods and strategies that make students interested in entrepreneurship, Berlin, the steps to realize entrepreneurship by 2% of the population can be realized.Research Objectives to Formulate a design model for entrepreneurial student development and model implementation. This type of research is qualitative research by issuing data using several methods, interviews, focus group discussions, surveys, methods of referring documents. The results of this study are new entrepreneurial models from the 2017 Usahid Student entrepreneurship program that emerged 4 New Entrepreneurs and there is a need for continuous assistance so as not to stop being stretched the road.